Conceptual analysis of suffering in cancer: a systematic review. Issue 9 (9th March 2015) - Best, Megan; Aldridge, Lynley; Butow, Phyllis; Olver, Ian; Webster, Fleur
Abstract Objective Patient suffering is a neglected area of care, partly because of poor definitions. The aim of this study was to distill what is currently known about suffering in the health literature in order to generate a conceptual basis for further research. Methods A systematic review focusing on suffering across all cancers was undertaken. The search included peer‐reviewed English articles published between 1992 and 2012 in MEDLINE, Embase, PsycINFO and the Cochrane Library databases focusing on conceptualisation of suffering in adult cancer patients. Seminal theoretical articles conceptualising suffering more generally were also eligible. To ensure identification of a sufficiently broad range of conceptualisations of suffering in cancer, the search strategy was drafted iteratively. Study findings were subjected to conceptual analysis using the evolutionary method. Results One hundred twenty‐eight studies were identified, which discussed definitions or conceptualisations of suffering. In terms of its attributes, suffering is defined as 'an all‐encompassing, dynamic, individual phenomenon characterized by the experience of alienation, helplessness, hopelessness and meaninglessness in the sufferer which is difficult for them to articulate. It is multi‐dimensional and usually incorporates an undesirable, negative quality.' Surrogate terms, antecedents and consequences of suffering are described. Conclusions The systematic review revealed that suffering includes holistic suffering, which is multidimensional, oscillating, individual and difficult for individuals to express. Opportunities should be provided for patients to express their suffering. The potential for suffering to be transcended needs to be recognized and facilitated by healthcare staff. Copyright © 2015 John Wiley & Sons, Ltd.